The association between the dietary index for gut microbiota and frailty: a cross-sectional study - Shouxin Wei; Sijia Yu; Meng Sun (Frontiers in Nutrition)
BackgroundFrailty severely impacts patients’ quality of life and imposes a significant burden on healthcare systems. The Dietary Index for Gut Microbiota (DI-GM) is an emerging dietary indicator, and its association with frailty has not been thoroughly investigated.MethodsThis study utilized data from NHANES 2007–2018 and assessed the association between DI-GM and frailty using multivariable weighted logistic regression, restricted cubic splines (RCS), subgroup analysis, and mediation analysis, after adjusting for relevant covariates.ResultsThe results indicate a significant negative correlation between DI-GM and frailty, with each standard unit increase in DI-GM reducing the risk of frailty by 6% (OR = 0.940 [0.899, 0.984]). DI-GM at different quartiles showed a strong dose–response relationship, with the highest quartile showing a 21.6% risk reduction. RCS analysis revealed a linear relationship between DI-GM and frailty. Subgroup analysis suggested that age and smoking status may influence the association between DI-GM and frailty. Furthermore, albumin and high-density lipoprotein (HDL) played significant mediating roles in the relationship between DI-GM and frailty, accounting for 30.34 and 9.05% of the total effect, respectively.ConclusionDietary Index for Gut Microbiota is negatively associated with frailty risk, and albumin and HDL mediate this association. Improving dietary quality may be an effective strategy for reducing frailty risk.